Prevalência e fatores de risco de anticorpos anti-Neospora Caninum em fêmeas bovinas leiteiras da agricultura familiar no município de Ji-Paraná, Rondônia - Vilas Boas, Ricardo (2014)
The neosporosis is considered a parasitic disease leading cause of abortion in cattle worldwide. The aim of this study was to investigate the prevalence of antibodies anti- Neospora caninum of dairy cows and associate to possible risk factors infection. 621 serum samples taken from dairy cows on 63 familiar agriculture farms in the county of Ji-Paraná, in the main milk producing region of Rondônia, Brazil, were evaluated by means Immunofluorescence Assay (IFAT). Samples were considered positive with a titer 100. Among all the samples analyzed (66/621), the prevalence was 10.61% (IC 95% 8,04-13,86%). The titers of antibodies ranging between 100 and 1600, distributed as follows: 22 (33.33%) serum samples had titers of 100, 21 (31.82%) title 200; 16 (24.24%) title 400, three (4.55%) title 800 and of four (6.06%) samples had titers of 1600. The prevalence of anti-N. caninum in farms was 60.31% (38/63), It is concluded that the dairy cows in the area studied are exposed to infection by N. caninum and that the presence of reproductive problems, such as abortion, and weak calves born are associated with the occurrence of neosporosis in cattle in the county.